2015
DOI: 10.1111/jan.12724
|View full text |Cite
|
Sign up to set email alerts
|

Organizational impact of nurse supply and workload on nurses continuing professional development opportunities: an integrative review

Abstract: Culture, leadership and workload issues impact nurses' ability to attend continuing professional development. The consequences affect competence to practice, the provision of safe, quality patient care, maintenance of professional registration, job satisfaction, recruitment and retention. Organizational leadership plays an important role in supporting attendance at continuing professional development as an investment for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
142
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 68 publications
12
142
0
5
Order By: Relevance
“…[27] Other studies showed that environment with full of career advancement opportunity could provide career advancement for nurses. [4][5][6][7] Moran reported that environment without advancement opportunities block nurses' development. [28] Munro reported that participants considered lack of support in the working environment a barrier to nurses' career advancement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[27] Other studies showed that environment with full of career advancement opportunity could provide career advancement for nurses. [4][5][6][7] Moran reported that environment without advancement opportunities block nurses' development. [28] Munro reported that participants considered lack of support in the working environment a barrier to nurses' career advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that healthy working environments make possible nurses to participate in continuing education. [6] Schmalenberg found that continuing education in nurses' working environment results in increasing their clinical competences, so that nurses with Master's degree are effective in creating such environments. [27] Other studies showed that environment with full of career advancement opportunity could provide career advancement for nurses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations